Winter Is Coming: Conserving Body Protein in Female Reindeer, Caribou, and Muskoxen - Barboza, Perry S.; Shively, Rachel D.; Gustine, Dave D.; Addison, J. A. (Frontiers in Ecology and Evolution, 2020)
Northern ungulates undergo pregnancy in winter when food supplies are low. Consequently, females employ a capital breeding strategy that relies upon maternal body stores of energy and protein for fetal growth. We studied captive female reindeer (Rangifer tarandus tarandus; n = 6; 118 kg), caribou (R. t. granti; n = 6; 97 kg), and muskoxen (Ovibos moschatus; n = 8; 205 kg) in late winter (February to April) to track body protein use in late pregnancy when feeding is often interrupted by snow storms and when wild animals begin movements to spring and summer ranges where they give birth. We used high and low protein rations (14-16% and 8% protein) as complete diets for Rangifer and high protein ration as a supplement (500g/day) to hay (7.3% protein; δ15N = 1.1‰) for Ovibos. Animals were fasted for 2 days to evaluate isotopic responses to an acute deficit of energy and protein on each diet in a sequence from δ15N 1.6‰, to 6.9‰ to 3.2‰ over 58 days. Dietary shifts in δ15N were reflected in plant fibers in the feces (fecal fiber) but not in blood cells (Rangifer 6.5 ± 0.3‰; Ovibos 5.2 ± 0.1‰). Serum proteins were higher in δ15N than blood cells whereas serum amino acids were lower in δ15N than blood cells and more responsive to changes in dietary δ15N indicated by fecal fiber. Fasting did not affect δ15N of serum proteins or serum amino acids. Values for δ15N in urea were strongly affected by both shifts in diet and by fasting, which indicated that excretory urea N was derived from cellular proteins and isotopically heavy proteins released from organs into the serum. Inter-organ exchanges of transport proteins may minimize oxidation of stored amino acids and conserve body protein stores for fetal growth and milk production in Rangifer and Ovibos. A capital breeding strategy in these long-lived, iteroparous herbivores relies upon routing of body proteins to simultaneously sustain both maternal function and maternal investment through common metabolic pathways that conserve lean body mass for survival.